The economic burden of cancer care for Syrian refugees: a population-based modelling study. Issue 5 (May 2020) - Abdul-Khalek, Rima A; Guo, Ping; Sharp, Forbes; Gheorghe, Adrian; Shamieh, Omar; Kutluk, Tezer; Fouad, Fouad; Coutts, Adam; Aggarwal, Ajay; Mukherji, Deborah; Abu-Sittah, Ghassan; Chalkidou, Kalipso; et al.
Summary: Background: Cancer represents a substantial health burden for refugees and host countries. However, no reliable data on the costs of cancer care for refugees are available, which limits the planning of official development assistance in humanitarian settings. We aimed to model the direct costs of cancer care among Syrian refugee populations residing in Jordan, Lebanon, and Turkey. Methods: In this population-based modelling study, direct cost per capita and per incident case for cancer care were estimated using generalised linear models, informed by a representative dataset of cancer costs drawn from 27 EU countries. A range of regression specifications were tested, in which cancer costs were modelled using different independent variables: gross domestic product (GDP) per capita, crude or age-standardised incidence, crude or age-standardised mortality, and total host country population size. Models were compared using the Akaike information criterion. Total cancer care costs for Syrian refugees in Jordan, Lebanon, and Turkey were calculated by multiplying the estimated direct cancer care costs (per capita) by the total number of Syrian refugees, or by multiplying the estimated direct cancer costs (per incident case [crude or age-standardised]) by the number of incident cancer cases in Syrian refugee populations. All costs are expressed in 2017 euros (€). Findings: Total cancer care costs for all 4·74 million Syrian refugees in Jordan, Lebanon, and Turkey in 2017 were estimated to be €140·23 million using the cost per capita approach, €79·02 million using the age-standardised incidence approach, and €33·68 million using the crude incidence approach. Under the lowest estimation, and with GDP and total country population as model predictors, the financial burden of cancer care was highest for Turkey (€25·18 million), followed by Lebanon (€6·40 million), and then Jordan (€2·09 million). Interpretation: Cancer among the Syrian refugee population represents a substantial financial burden for host countries and humanitarian agencies, such as the UN Refugee Agency. New ways to provide financial assistance need to be found and must be coupled with clear, prioritised pathways and models of care for refugees with cancer. Funding: UK Research and Innovation Global Challenges Research Fund: Research for Health in Conflict-Middle East and North Africa region (R4HC-MENA).